A study on traditional practice of squeezing of breasts in newborn care among mothers in a tertiary care centre in Malda, West Bengal, India - Sahoo, Sushama; Singh, Arpita (International Journal Of Community Medicine And Public Health, 2021)
Background: Newborn care is culturally and traditionally sensitive in every society. India is a vast country with different communities having their own traditional practices of newborn care. Squeezing of breasts in newborn period is one such unique traditional practice prevalent among population of rural background of West Bengal. This study was conducted to explore the traditional practice of squeezing of neonatal breasts and to highlight its related morbidities following the procedure among newborns. Methods: This was a descriptive, cross-sectional study conducted at triage of Special Newborn Care Unit (SNCU) of Malda Medical College and Hospital among 352 mothers who presented to us with their sick newborns following squeezing of neonatal breasts. After obtaining proper informed consent, mothers were interviewed. The data were collected using pre-designed questionnaires. Statistical analyses of the data were done using SPSS version 21. Results: In the present study, majority (33.52%) of mothers were 18-21 years old and 92.90% were Muslims. Squeezing of neonatal breasts was usually done on 10th day of life (40.34%) and on 4th day of life (27.27%). Local application following squeezing was done with hot turmeric paste (31.25%) and mustard oil (27.56%). Majority of newborns presented with features of mastitis (39.49%), 15.91% with breast abscess and 35.51% with sepsis. Conclusions: This study highlights the harmful aspects of traditional practice of breasts-squeezing among newborns prevalent in rural Bengal. This practice must be condemned by everyone through an integrated approach of proper health education and counseling of mothers and family members.